2017
DOI: 10.1002/ldr.2781
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon and Nutrient Dynamics Following Cessation of Anthropogenic Disturbances in Degraded Subtropical Forests

Abstract: Soil carbon (C) and nutrient availability is fundamental to terrestrial biodiversity and functionality. In recent decades, the restoration of degraded forests has become a major concern worldwide, and recent studies have demonstrated that soil C and nitrogen (N) increase over time following restoration. However, our understanding of the responses of soil phosphorus (P), calcium (Ca), potassium (K) and magnesium (Mg) and elemental stoichiometric ratios to restoration remains elusive. We employed a chronosequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 57 publications
(100 reference statements)
0
26
0
Order By: Relevance
“…Our results indicate that cessation of anthropogenic disturbances in the highly degraded forests, despite that they were also dominated by trees prior to restoration, could double FR biomass and production within 6 years after closure. Given the strong contributions of roots and root‐associated microorganisms to soil carbon (Clemmensen et al, ; Jackson et al, ; McCormack et al, ; Yuan et al, ), our finding indicates a profound contribution of China's large‐scale closure (Feng et al, ; Ouyang et al, ) to the carbon sequestration and nutrient cycling of China's forests and their global contributions. Our results offer a new and important understanding of the importance of ecological restoration to ecosystem function.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Our results indicate that cessation of anthropogenic disturbances in the highly degraded forests, despite that they were also dominated by trees prior to restoration, could double FR biomass and production within 6 years after closure. Given the strong contributions of roots and root‐associated microorganisms to soil carbon (Clemmensen et al, ; Jackson et al, ; McCormack et al, ; Yuan et al, ), our finding indicates a profound contribution of China's large‐scale closure (Feng et al, ; Ouyang et al, ) to the carbon sequestration and nutrient cycling of China's forests and their global contributions. Our results offer a new and important understanding of the importance of ecological restoration to ecosystem function.…”
Section: Discussionmentioning
confidence: 61%
“…Compared with tree plantation establishment, closure is more cost‐effective for restoring degraded forests (Ma, Lv, & Li, ; Xu et al, ). Previous studies have shown that tree canopy cover and stand basal area increase quickly (Xu et al, ), canopy dominance shifts from early‐ to late‐successional tree species (Hou, R‐d, B‐w, & Wang, ), and soil carbon concentration and pool size increase (Feng, Ma, Fu, & Chen, ) over time following closure. Although restoring ecosystem productivity is regarded as an important criterion for success (Ruiz‐Jaen & Aide, ), the effect of mountain closure on ecosystem productivity has rarely been examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Luna et al (), application of organic amendment enhanced soil structure and infiltration and reduced soil losses by erosion. The development of rooting systems, addition of biomass, and slight anthropogenic perturbation after reclamation improved soil structure, increased porosity, and decreased soil bulk density (Akala & Lal, ; Feng, Ma, Fu, & Chen, ; Luna et al, ). In their study, Luna et al () made similar observation of increasing soil moisture along the chronosequence.…”
Section: Discussionmentioning
confidence: 99%
“…In mountainous forest regions, the vegetation and soil parameters were investigated to evaluate forest degradation at the field level. Forest degradation caused reduced vegetation and increased soil disturbances, such as damaged biodiversity and a reduction in soil carbon and nutrients (Cao, ; Feng, Ma, Fu, & Chen, ). Combined with the study area's local situation, we considered commonly accepted indicators related to degradation, such as canopy density, the diversity index (Shannon's diversity index), soil physical properties (soil moisture and soil bulk density), soil organic matter, and soil total nitrogen (Cowie et al, ; Kairis et al, ).…”
Section: Methodsmentioning
confidence: 99%